ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI UNDERPRICING KETIKA INITIAL PUBLIC OFFERING (IPO) DI BURSA EFEK INDONESIA - Indita Azisia Risqi; Puji Harto (Diponegoro Journal of Accounting, 2013)
Underpricing is phenomenon of IPO which often happened in capital market and have been proved by researchers in many countries. This research aims to analyze the determinant factors of underpricing. The population research was company go public which is listed on Bursa Efek Indonesia (BEI) which perform initial public offering (IPO). Samples in this study were an IPO company listed on the Stock Exchange (Indonesia Stock Exchange) in the 2007-2011 period. The samples used were 71 companies that were taken through purposive sampling. The results of this research showed that underwriter's reputation has negative and significant effect on underpricing. While the auditor's reputation, Return on Equity (ROE) and leverage ratio has no effect on underpricing.